Report of Workshops entitled, 'Using COUNTER statistics: a practical perspective' held at UKSG Conference 2004 - Bevan, Simon J.; Jones, Louise (Cranfield University, 2004)
This is a report from three workshops run jointly by Simon Bevan (Cranfield University) and Louise Jones (University of Leicester).
Keywords: COUNTER project